High hepatitis B and low hepatitis C prevalence in Roma population in eastern Slovakia - Veselíny, Eduard; Janicko, Martin; Drazilová, Sylvia; Siegfried, Leonard; Pastvová, Lýdia; Schréter, Ivan; Kristian, Pavol; Viág, Ladislav; Jarcuska, Pavol; Valková, Ivana; Cáriková, Katarína; Senajová, Gabriela; et al. (Central European journal of public health, 2014)
BACKGROUND: Viral hepatitis B and C prevalence in the Roma population of eastern Slovakia is largely unknown. This study aimed to explore the prevalence and associated risk factors of chronic viral hepatitis B and C among Roma living in segregated communities in eastern Slovakia. METHODS: Data from the cross-sectional HepaMeta study conducted in Slovakia in 2011 among Roma living in rural communities were used. Participants were tested for the presence of HBsAg, anti-HBc IgG and anti-HCV. The risk factors were assessed mainly via a structured questionnaire/interview. RESULTS: Altogether 452 Roma were screened, and 11 were excluded due to missing data. A total of 441 patients were included (mean age 34.7 +/- 9.14 years; 35.2% men). 12.5% of participants were HBsAg positive, 40.4% anti-HBc IgG positive while negative for HBsAg and 47.2% of participants were negative for all serological markers of hepatitis B. Hepatitis C prevalence was very low (0.7%), while 2 out of 3 anti-HCV positive participants were coinfected with hepatitis B. Risk factors for hepatitis B infection were male sex, higher age, tattoo, and previous imprisonment. No difference was found in intravenous drug use, blood transfusions and sexual behaviour. CONCLUSION: More than half of the Roma residing in eastern Slovakia have been infected at one point in life with the hepatitis B virus, and 12.5% are HBsAg positive. Hepatitis C prevalence is very low, which is probably due to very low intravenous drug use.
Keywords: Young Adult; hepatitida C; Cross-Sectional Studies; Comorbidity; Male; Rural Population; Slovakia; Slovenská republika; Risk Factors; mladý dospělý; Health Surveys; Adolescent; Roma; chronická nemoc; Adult; prevalence; venkovské obyvatelstvo; dospělí; mužské pohlaví; Romové; Chronic Disease; průzkumy a dotazníky; Hepatitis B; mladiství; komorbidita; lidé; ženské pohlaví; Humans; Hepatitis C; rizikové faktory; průřezové studie; zdravotnické přehledy; Prevalence; hepatitida B; Age Distribution; věkové rozložení; Female; Surveys and Questionnaires; lidé středního věku; Middle Aged